Keanekaragaman Tumbuhan Paku (Pteridophyta) Di Sekitar Kawasan Universitas Negeri Padang Air Tawar Barat - Siti Sahara; serli sri wahyuni; S Syamsurizal (Biology Study Program, Faculty of Science and Engineering, University of Bangka Belitung, Indonesia, 2025)
Ferns (Pteridophyta) are an important component of the ecosystem, contributing to biodiversity and environmental stability. Padang State University Air Tawar Barat area has the potential for fern diversity that has not been fully explored. This study aims to describe the diversity and distribution of ferns in the area. The method used was descriptive-explorative with sampling in 20 plots measuring 5 m x 5 m. The results showed that there were nine species belonging to five families, with a diversity index of 1.96 which is classified as moderate. Pyrrosia piloselloides species was found to be the most dominant. This level of diversity is lower compared to studies in other locations, due to the influence of human activities on the habitat. Environmental factors such as neutral soil pH, relatively warm temperatures and high humidity favor the growth of ferns. These findings emphasize the importance of understanding the relationship between abiotic factors and species diversity, as well as the need for conservation efforts to maintain ecosystems in the West Freshwater State University area.